Work-related musculoskeletal disorders among dental staff in south Malaysia - Kumareswaran, Suriya; Muhadi, Siti Umairah; Retnam, Sathiya Kumaran Vijaya; Sathasivam, Jeyanthini; Sundram, Bala Murali (International Journal of Public Health Science (IJPHS), 2023)
The dental industry poses ergonomic health concerns, leading to work-related musculoskeletal disorders (MSD) among staff. This study aims to assess MSD incidence and related sociodemographic and occupational hazard factors among dental practitioners in Johor, Malaysia. A cross-sectional investigation in December 2022 included 382 dental officers from government and commercial sectors. Participants comprised 79.2% females, 72.3% Malays, 97.4% non-smokers, and 92.4% working in dental clinics. MSD was most prevalent in the neck, shoulder, and lower back regions. Logistic regression revealed higher neck pain probability among smokers and a positive association between back pain and standing while working. Poisson regression indicated an inverse relationship between exercise frequency and MSD pain occurrence. Regular physical activity correlated with lower body mass index (BMI) and reduced MSD pain. The study underscores the importance of ergonomic interventions and promoting exercise to prevent MSD and enhance the well-being of dental staff in Johor, Malaysia. Understanding the factors contributing to MSD among dental practitioners is crucial for implementing effective preventive measures and improving overall occupational health in the dental industry.